Comparison of Pre-emptive Analgesic Effect of Paracetamol, Ibuprofen, and Placebo in Reducing Post-operative Pain in Intra-alveolar Tooth Extraction at The University of Benin Teaching Hospital, Benin City. A Randomised Trial. - Mercy Okoh; JOSEPHINE OMO OWOLABI; PETER E EGBOR (Nigerian Dental Association, 2024)
Objective: Pain is one of the most common postoperative complications of extraction. Thus, this study is aimed at determining the pre-emptive effectiveness of paracetamol and ibuprofen in the management of post extraction pain. Methods: A randomized, placebo‐controlled, single‐blinded comparative study of patients who needed intra-alveolar extraction of posterior teeth. Sixty‐nine patients aged 18 years and above were randomly assigned to one of three groups: (A) paracetamol 1g; (B) ibuprofen 400mg; and (C) placebo (calcium lactate) 300mg. Each of the three tablets was given 30 minutes before administration of the local anesthetic agent. The pain level was assessed using the visual analogue scale®. Chi-square (X²) test, one-way analysis of variance (ANOVA) with an appropriate post-hoc test was used. Level of significance was set at 95% (p-value < 0.05). Results: Ibuprofen and paracetamol groups showed lower pain scores compared to placebo.  Although, there was no significant difference between the VAS scores at the post-operative period (P= 0.080). There was a significant difference in time taken for use of rescue medication among the three groups (p = 0.022), with those in placebo group 8 times more likely to use rescue medication relative to the analgesics. Conclusion: The use of preemptive analgesics showed lower pain scores compared to placebo, and also significantly increased the time for use of rescue medication postoperatively.